Participation Patterns in Leisure Activities of 6- to 8-Year-Old Typically Developing Children in Relation to Their Motor Performance - Habluetzel Esposito, Elisa; Derikx, Dagmar F. A. A.; Houwen, Suzanne; Schoemaker, Marina M.; Hartman, Esther (Research quarterly for exercise and sport, 2025)
The average level of children's motor performance has decreased in the past decades. Therefore, it is important to identify risk- or enabling factors for motor performance. One such factor could be children's participation in leisure activities (LA). LA are non-obligatory and intrinsically motivated activities performed during free time. They include physical activities, such as individual and team sports and other types of activities, such as doing crafts, hanging out with friends, and playing musical instruments. The present study explores how participating in different combinations of LA (i.e. participation patterns) are related to children's motor performance using a person-centered approach. Ninety 6- to 8-year-old typically developing children (57.8% boys) were recruited from six Dutch primary schools. LA participation and motor performance were measured with the Children's Assessment of Participation and Enjoyment questionnaire and the Movement Assessment Battery for Children-2, respectively. Children were grouped in patterns using Cluster Analysis. Comparisons among patterns were performed with one-way multivariate analysis of variance. As hypothesized, children who participated in a greater variety of LA (i.e., higher participation diversity) and who engaged more frequently in each LA (i.e., higher participation intensity) scored better on manual dexterity, balance, and total motor performance compared to those with lower participation diversity and intensity. Based on these findings, coaches, physical educators, and parents should create opportunities for children to participate in a broad range of LA and to engage in these LA frequently.